Bahasa Laiyolo, Rumpun Muna-Buton yang Terancam Punah - Rahmawati Rahmawati (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
Laiyolo language is a language located in the administrative area of South Sulawesi Province, namely in Selayar Regency. However, this language is classified into the Muna- Buton language group located in Southeast Sulawesi. As Esser (1938) informed, the Muna-Buton group consists of (a) Muna-Buton, (b) South Buton, (c) Artisan island group (Kalaota, Larompa, Bonerate), (d) Wolio-Laiyolo. This kinship relationship study was carried out using two approaches both qualitatively and quantitatively. Quality approach with lexicostatistical techniques that explain the kinship relations of the three languages. The qualitative approach is aimed at providing evidence of kinship relations between the three languages with criteria for joint innovation in the fields of phonology and lexicon. The Laiyolo language is endangered. Based on data in 2010, the number of Laiyolo speakers is no more than 10 people who are around 40 years old. The younger generation no longer speaks the Laiyolo language. However, they switched to the national language and Selayar which is the majority language. Thus, efforts to revitalize the Laiyolo language need to be carried out immediately before this language experiences a very critical condition.